Dampak Profitabilitas Sebagai Variabel Moderasi terhadap Pengaruh Praktik Tata Kelola Perusahaan Yang Baik dan Tanggung Jawab Sosial Perusahaan Terhadap Nilai Perusahan: Studi Empiris pada Perusahaan Sub Sektor Retailing yang Terdaftar pada Bursa Efek Indonesia Periode 2019 – 2023 - Muhamad Soleh Rizky; Prita Andini (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This study was conducted to examine the influence of good corporate governance with proxies by managerial ownership, institutional ownership and independent commissioners as well as corporate social responsibility with profitability as a moderation variable on company value. The sample selection technique in this study uses purposive sampling and was obtained from 11 retail companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The data analysis used in this study is multiple linear regression analysis using SPSS software version 27. Based on the results of the study, it can be concluded that managerial ownership and CSR have no effect on company value, institutional ownership and independent commissioners have a positive effect on company value, profitability cannot moderate the influence of managerial ownership and CSR on company value, and profitability can weaken the influence of institutional ownership and independent commissioners on company value.